Indole-Based Small Molecules as Potential Therapeutic Agents for the Treatment of Fibrosis - Qin, Rui; Zhao, Qian; Han, Bo; Zhu, Hong-Ping; Peng, Cheng; Zhan, Gu; Huang, Wei (Frontiers in Pharmacology, 2022)
Indole alkaloids are widely distributed in nature and have been particularly studied because of their diverse biological activities, such as anti-inflammatory, anti-tumor, anti-bacterial, and anti-oxidant activities. Many kinds of indole alkaloids have been applied to clinical practice, proving that indole alkaloids are beneficial scaffolds and occupy a crucial position in the development of novel agents. Fibrosis is an end-stage pathological condition of most chronic inflammatory diseases and is characterized by excessive deposition of fibrous connective tissue components, ultimately resulting in organ dysfunction and even failure with significant morbidity and mortality. Indole alkaloids and indole derivatives can alleviate pulmonary, myocardial, renal, liver, and islet fibrosis through the suppression of inflammatory response, oxidative stress, TGF-β/Smad pathway, and other signaling pathways. Natural indole alkaloids, such as isorhynchophylline, evodiamine, conophylline, indirubin, rutaecarpine, yohimbine, and vincristine, are reportedly effective in organ fibrosis treatment. In brief, indole alkaloids with a wide range of pharmacological bioactivities are important candidate drugs for organ fibrosis treatment. The present review discusses the potential of natural indole alkaloids, semi-synthetic indole alkaloids, synthetic indole derivatives, and indole-contained metabolites in organ fibrosis treatment.